Electronic grade copper sulfate and purification method and application thereof
By using ammonia water to adjust the pH value, activated carbon oil removal and control recrystallization yield during the copper sulfate purification process, the problems of silver sulfate purity and impurity content in the prior art were solved, and the purification of high-purity copper sulfate was achieved, which was suitable for high-demand applications in the electronics industry.
Patent Information
- Application Number
- CN202410891236.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-04
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-07-04
AI Technical Summary
The existing oxidative neutralization method is difficult to achieve a copper sulfate purity of more than 99.9%, and contains high amounts of metal impurities such as Fe, Ti and total organic carbon, which cannot meet the use requirements of electronic grade copper sulfate.
The pH value is adjusted to 3.5-4 with precipitant agents such as ammonia water, and impurities such as Fe and Ti are removed, then the oil is removed by activated carbon, and finally recrystallization is carried out, and the crystal yield is controlled ≤60% to obtain high-purity copper sulfate.
It achieves high purity (≥99.999%) and low impurity content of copper sulfate, and is suitable for nano-scale chip integrated circuit field, ensuring high electroplating activity, fast speed, and obtaining a uniform and stable plating layer.
Smart Images

Figure CN118954570B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical processes, and in particular relates to electronic-grade copper sulfate and a purification method and application thereof. Background Art
[0002] Copper sulfate is an important copper salt among copper compounds and is widely used in the chemical industry, such as electroplating, catalysis and preparation of chemicals. With the rapid development of the electroplating industry and the printed circuit board industry, the demand for copper sulfate has increased rapidly, and strict requirements have been put forward for the quality of copper sulfate products. Since industrial-grade crude copper sulfate inevitably contains organic impurities and various metal and non-metal impurities to varying degrees, using it without removing these impurities will seriously affect the quality of electronic products. For example, when electronic components such as printed circuit boards are chemically plated, the plating solution used is very sensitive to impurities. Organic and non-metallic impurities will reduce the activity of the plating solution, resulting in a decrease in the chemical plating speed and leakage plating. In severe cases, the chemical plating process will be completely stopped; various metal impurities will lead to reduced plating speed, darkening of the coating, leakage plating, etc., and deposition on the coating will cause the coating to be unstable and rough. Therefore, electronic-grade copper sulfate has become a key electronic chemical in the electronics industry.
[0003] At present, the purification methods of copper sulfate mainly include oxidation neutralization, electrolysis, recrystallization and extraction. Among them, oxidation neutralization is a method that is easy to operate, low in cost and high in efficiency, but the copper sulfate product purity obtained by the current oxidation neutralization method is low, and it is difficult to reach more than 99.9%. The total content of metal impurities is high, especially containing a large amount of metal impurities such as Fe, Ti and total organic carbon (TOC), which is difficult to meet the use requirements of electronic grade copper sulfate. For example, the current oxidation neutralization method usually uses sodium carbonate or sodium hydroxide for neutralization. Although it can quickly achieve pH adjustment to 2-3, a large amount of copper ions will also be directly precipitated, and residual Na ions will remain in the system and affect the purity of copper sulfate crystals during the final concentrated crystallization.
[0004] Therefore, it is currently necessary to find a method for purifying copper sulfate to obtain copper sulfate with high purity and low impurity content. Summary of the invention
[0005] In order to overcome at least one problem of the above-mentioned prior art, one of the objects of the present invention is to provide a method for purifying copper sulfate, wherein the copper sulfate obtained by the method has high purity and low impurity content.
[0006] A second object of the present invention is to provide electronic grade copper sulfate obtained by the above purification method.
[0007] The third object of the present invention is to provide an application of the electronic grade copper sulfate in the field of nano-scale chip integrated circuits.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] A first aspect of the present invention provides a method for purifying copper sulfate, comprising the following steps:
[0010] S1, impurity removal: adding a precipitant to the oxidized copper sulfate crude solution, adjusting the pH value to 3.5-4, and obtaining a copper sulfate impurity removal solution after solid-liquid separation; the precipitant includes at least one of ammonia water, ammonium bicarbonate, ammonium carbonate, copper hydroxide or basic copper carbonate;
[0011] S2, degreasing: removing the oil from the copper sulfate impurity removal liquid by adsorption to obtain a copper sulfate purified liquid;
[0012] S3, recrystallization: evaporating and concentrating the copper sulfate purification liquid, cooling and crystallizing, controlling the crystal yield to be ≤60%, and obtaining purified copper sulfate.
[0013] The invention firstly uses a precipitant to remove impurities from an oxidized copper sulfate crude solution, and adjusts the pH value to 3.5-4 to mainly remove most of Fe, Ti impurities and part of other impurities, while ensuring that copper ions do not form precipitation, and the precipitant used in this step has a good pH adjustment effect and does not introduce additional metal impurities, and does not have a negative impact on subsequent purification; then, adsorption deoiling is performed to remove most of TOC, and the removal effect is good; finally, recrystallization is performed, and it is necessary to control the crystal yield to be less than or equal to 60%. If the yield is too high, the impurity removal rate will be reduced, which affects the final purification effect. Through the cooperation of the above steps, a copper sulfate product with high purity and low impurity content can be obtained.
[0014] In some embodiments of the present invention, in step S1, the precipitant includes at least one of aqueous ammonia, ammonium bicarbonate or ammonium carbonate; in some specific embodiments of the present invention, in step S1, the precipitant is selected from aqueous ammonia.
[0015] In the purification system of the present invention, the ability of ammonia water to adjust pH is stronger than that of ammonium bicarbonate or ammonium carbonate, and the amount used will be less. Using ammonia water as a precipitant can obtain a better purification effect.
[0016] In some embodiments of the present invention, in step S1, the pH value is adjusted to 3.6-3.8. At this pH value, Fe and Ti have a good removal effect and are conducive to reducing the precipitation of copper ions.
[0017] In some embodiments of the present invention, in step S1, the crude copper sulfate solution contains copper element and metal impurity elements, and the metal impurity elements include at least one of iron, titanium, aluminum, calcium, chromium, cobalt, indium, lead, magnesium, manganese, nickel, potassium, sodium, tin or zinc.
[0018] In some embodiments of the present invention, in step S1, the copper content of the crude copper sulfate solution is 75-95 g / L; in some specific embodiments of the present invention, the copper content of the crude copper sulfate solution is 80-90 g / L; non-limiting examples are 82 g / L, 85 g / L or 88 g / L.
[0019] In some embodiments of the present invention, in step S1, the oxidant used in the oxidation is selected from hydrogen peroxide.
[0020] In some embodiments of the present invention, in step S1, the mass ratio of the oxidizing agent added by oxidation to the crude copper sulfate solution is 1:(100-400); in some specific embodiments of the present invention, the mass ratio of the oxidizing agent added by oxidation to the crude copper sulfate solution is 1:(120-380); non-limiting examples are 1:150, 1:200, 1:300 or 1:350.
[0021] In some embodiments of the present invention, the mass ratio of the precipitant to the crude copper sulfate solution is 1:(150-350); in some specific embodiments of the present invention, the mass ratio of the precipitant to the crude copper sulfate solution is 1:(200-300); non-limiting examples are 1:220, 1:250 or 1:280.
[0022] Adding too much oxidant or precipitant will dilute the copper ion concentration, affecting the yield and purification effect of subsequent recrystallization. Adding too little will result in poor impurity removal effect. Adding an appropriate amount of oxidant and precipitant is conducive to better purification effect. In addition, too much precipitant will also cause copper ions to precipitate and affect the purification effect.
[0023] In some embodiments of the present invention, in step S1, an oxidant is first added to carry out an oxidation reaction, and then a precipitant is added to carry out a precipitation reaction.
[0024] First, an oxidant is used to oxidize the metal impurity ions to a higher valence state, which is conducive to the formation of precipitation and removal, especially the oxidation of Fe and Ti to a high valence state. Then, the pH value is adjusted by a precipitant to make Fe and Ti reach a better precipitation state, achieve a higher removal rate, and will not precipitate copper ions to cause loss of target products.
[0025] In some embodiments of the present invention, the oxidation reaction time is 0.5 to 2 hours; non-limiting examples are 0.8 hours, 1 hour, 1.5 hours or 1.8 hours.
[0026] In some embodiments of the present invention, the reaction time after adding the precipitant is 1 to 10 hours; non-limiting examples are 2 hours, 4 hours or 8 hours.
[0027] In some embodiments of the present invention, the precipitation reaction is followed by static sedimentation to allow the precipitate to settle sufficiently for subsequent separation, and the static sedimentation time may be 8 to 12 hours.
[0028] In some embodiments of the present invention, in step S2, oil is removed by activated carbon.
[0029] In some embodiments of the present invention, in step S2, the specific surface area of the activated carbon is 1000-1500m 2 / g; a non-limiting example is 1100m 2 / g、1200m 2 / g、1300m 2 / g or 1400m 2 / g.
[0030] The use of activated carbon for adsorption and oil removal has a good effect on removing oily impurities such as total organic carbon. The use of activated carbon with a suitable specific surface area can effectively adsorb impurities and has a better oil removal effect.
[0031] In some embodiments of the present invention, in step S3, the crystal yield is controlled to be 20-60%; in some specific embodiments of the present invention, in step S3, the crystal yield is controlled to be 40-60%; non-limiting examples are 45%, 50% or 55%.
[0032] A high crystal yield will lead to a high impurity content, while a low crystal yield will result in fewer crystals, lower purification efficiency, and higher actual production costs. By controlling the crystal yield within an appropriate range, a higher crystal purity can be ensured while also having a higher purification efficiency.
[0033] In some embodiments of the present invention, in step S3, before evaporation and concentration, the pH value of the copper sulfate purification solution is adjusted to 1-2.
[0034] Adjusting the pH value of the system to a range of 1 to 2 before recrystallization can inhibit the hydrolysis of the copper sulfate solution and allow impurities that are easily soluble in acid to remain in the mother liquor, thereby improving the purity of the copper sulfate obtained by recrystallization.
[0035] In some embodiments of the present invention, sulfuric acid is used to adjust the pH value of the copper sulfate purification solution.
[0036] The use of sulfuric acid can adjust the pH of the system to be acidic on the one hand, and on the other hand will not introduce new impurity ions or groups.
[0037] In some embodiments of the present invention, the water used in each step is ultrapure water.
[0038] In some embodiments of the present invention, the conductivity of the ultrapure water is ≤1 μS; in some specific embodiments of the present invention, the conductivity of the ultrapure water is 0.1-1 μS; non-limiting examples are 0.3 μS, 0.5 μS, 0.7 μS or 0.9 μS.
[0039] In some embodiments of the present invention, the total content of metal impurities in the ultrapure water is ≤10 μg / L; in some specific embodiments of the present invention, the total content of metal impurities in the ultrapure water is 4-10 μg / L; non-limiting examples are 5 μg / L, 6 μg / L, 7 μg / L, 8 μg / L or 9 μg / L.
[0040] By controlling the purity of water, the introduction of impurities can be reduced and the purification effect can be improved.
[0041] The second aspect of the present invention provides electronic grade copper sulfate obtained by the purification method described in the first aspect of the present invention.
[0042] In some embodiments of the present invention, the purity of the electronic grade copper sulfate is ≥99.999%.
[0043] In some embodiments of the present invention, the total metal impurity content of the electronic grade copper sulfate is <1 mg / L.
[0044] In some embodiments of the present invention, the Fe content of the electronic grade copper sulfate is less than 110 μg / L.
[0045] In some embodiments of the present invention, the Ti content of the electronic grade copper sulfate is less than 110 μg / L.
[0046] In some embodiments of the present invention, the TOC content of the electronic grade copper sulfate is <3 mg / L.
[0047] The third aspect of the present invention provides an application of the electronic-grade copper sulfate described in the second aspect of the present invention in the field of nano-scale chip integrated circuits.
[0048] The electronic-grade copper sulfate provided by the invention has high purity, low total metal impurity content and low TOC content, high electroplating activity and fast electroplating speed when prepared into an electroplating solution for electroplating, and uniform quality and high stability of the obtained coating. Therefore, the electronic-grade copper sulfate of the invention has wide application in the field of nano-scale chip integrated circuits.
[0049] The invention has the following beneficial effects: the invention adopts a specific precipitant and adjusts the pH value of precipitation to a specific value, removes most of Fe and Ti impurities and part of other impurities, avoids loss caused by precipitation of copper ions, combines adsorption and oil removal to remove most of TOC impurities, and finally performs recrystallization to control a specific crystallization yield, so that the copper sulfate finally obtained has high purity, and the total content of metal impurities and TOC content are both low. The copper sulfate obtained by the invention is electronic grade copper sulfate, and has wide application in the field of nano-chip integrated circuits. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 This is the process flow chart of Example 1. DETAILED DESCRIPTION
[0051] The content of the present invention is further described in detail below through specific examples. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles set forth in the present invention all belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific data exemplified below. The raw materials, reagents or devices used in the following examples and comparative examples, unless otherwise specified, can all be obtained from conventional commercial sources, or can be obtained by existing known methods.
[0052] In some embodiments of the present invention, in step S1, the crude copper sulfate solution contains copper element and metal impurity elements, and the metal impurity elements include at least one of iron, titanium, aluminum, calcium, chromium, cobalt, indium, lead, magnesium, manganese, nickel, potassium, sodium, tin or zinc.
[0053] In some embodiments of the present invention, in step S1, the copper content in the crude copper sulfate solution is 75-95 g / L; in some specific embodiments of the present invention, the copper content in the crude copper sulfate solution is 80-90 g / L; non-limiting examples are 82 g / L, 85 g / L or 88 g / L.
[0054] In some embodiments of the present invention, in step S1, the iron content in the crude copper sulfate solution is 300-2000 μg / L; in some specific embodiments of the present invention, the iron content in the crude copper sulfate solution is 1200-2000 μg / L; non-limiting examples are 1500 μg / L, 1700 μg / L or 1900 μg / L.
[0055] In some embodiments of the present invention, in step S1, the titanium content in the crude copper sulfate solution is 300-2000 μg / L; in some specific embodiments of the present invention, the titanium content in the crude copper sulfate solution is 500-1200 μg / L; non-limiting examples are 600 μg / L, 700 μg / L or 1000 μg / L.
[0056] In some embodiments of the present invention, in step S1, the aluminum content in the crude copper sulfate solution is 100-500 μg / L; in some specific embodiments of the present invention, the aluminum content in the crude copper sulfate solution is 150-300 μg / L; non-limiting examples are 170 μg / L, 200 μg / L or 250 μg / L.
[0057] In some embodiments of the present invention, in step S1, the calcium content in the crude copper sulfate solution is 200-800 μg / L; in some specific embodiments of the present invention, the calcium content in the crude copper sulfate solution is 300-500 μg / L; non-limiting examples are 350 μg / L, 400 μg / L or 450 μg / L.
[0058] In some embodiments of the present invention, in step S1, the chromium content in the crude copper sulfate solution is 30-200 μg / L; in some specific embodiments of the present invention, the chromium content in the crude copper sulfate solution is 50-150 μg / L; non-limiting examples are 80 μg / L, 100 μg / L or 120 μg / L.
[0059] In some embodiments of the present invention, in step S1, the cobalt content in the crude copper sulfate solution is 3 to 30 μg / L; in some specific embodiments of the present invention, the cobalt content in the crude copper sulfate solution is 5 to 20 μg / L; non-limiting examples are 10 μg / L, 15 μg / L or 18 μg / L.
[0060] In some embodiments of the present invention, in step S1, the indium content in the crude copper sulfate solution is 10-40 μg / L; in some specific embodiments of the present invention, the indium content in the crude copper sulfate solution is 13-30 μg / L; non-limiting examples are 15 μg / L, 20 μg / L or 25 μg / L.
[0061] In some embodiments of the present invention, in step S1, the lead content in the crude copper sulfate solution is less than 1 μg / L.
[0062] In some embodiments of the present invention, in step S1, the magnesium content in the crude copper sulfate solution is 10-50 μg / L; in some specific embodiments of the present invention, the magnesium content in the crude copper sulfate solution is 20-40 μg / L; non-limiting examples are 24 μg / L, 30 μg / L or 35 μg / L.
[0063] In some embodiments of the present invention, in step S1, the manganese content in the crude copper sulfate solution is 1-20 μg / L; in some specific embodiments of the present invention, the manganese content in the crude copper sulfate solution is 5-15 μg / L; non-limiting examples are 7 μg / L, 10 μg / L or 12 μg / L.
[0064] In some embodiments of the present invention, in step S1, the nickel content in the crude copper sulfate solution is 5-40 μg / L; in some specific embodiments of the present invention, the nickel content in the crude copper sulfate solution is 10-30 μg / L; non-limiting examples are 15 μg / L, 20 μg / L or 25 μg / L.
[0065] In some embodiments of the present invention, in step S1, the potassium content in the crude copper sulfate solution is 300-1000 μg / L; in some specific embodiments of the present invention, the potassium content in the crude copper sulfate solution is 400-800 μg / L; non-limiting examples are 500 μg / L, 600 μg / L or 700 μg / L.
[0066] In some embodiments of the present invention, in step S1, the sodium content in the crude copper sulfate solution is 30-200 μg / L; in some specific embodiments of the present invention, the sodium content in the crude copper sulfate solution is 50-150 μg / L; non-limiting examples are 80 μg / L, 100 μg / L or 120 μg / L.
[0067] In some embodiments of the present invention, in step S1, the tin content in the crude copper sulfate solution is 1 to 15 μg / L; in some specific embodiments of the present invention, the tin content in the crude copper sulfate solution is 2 to 10 μg / L; non-limiting examples are 3 μg / L, 5 μg / L or 7 μg / L.
[0068] In some embodiments of the present invention, in step S1, the zinc content in the crude copper sulfate solution is 50-300 μg / L; in some specific embodiments of the present invention, the zinc content in the crude copper sulfate solution is 100-200 μg / L; non-limiting examples are 130 μg / L, 150 μg / L or 170 μg / L.
[0069] In some embodiments of the present invention, in step S1, the crude copper sulfate solution also contains TOC.
[0070] In some embodiments of the present invention, in step S1, the TOC content in the crude copper sulfate solution is 10-50 mg / L; in some specific embodiments of the present invention, the TOC content in the crude copper sulfate solution is 20-40 mg / L; non-limiting examples are 25 mg / L, 30 mg / L or 35 mg / L.
[0071] The following is a description with reference to specific embodiments.
[0072] In the following embodiments, ND means that when the content of a substance is lower than the minimum detection limit of the detection equipment, the substance will be marked as "ND" in the test report, indicating that the content of the substance is ≤0.01 μg / L.
[0073] In the following examples, the detected metal impurities include iron, titanium, aluminum, calcium, chromium, cobalt, indium, magnesium, manganese, nickel, potassium, sodium, tin and zinc. The total content of metal impurities (total metal impurities) is the sum of the contents of the above metal impurities. Copper is not a metal impurity.
[0074] The crude copper sulfate used in the following examples is an anhydrous copper sulfate crystal raw material, in which the copper content is 25.3wt%. The components and contents of the crude copper sulfate solution obtained by dissolving the crude copper sulfate in ultrapure water are shown in Table 1 (the units of the contents of some components are separately marked, and the units of the contents of other unmarked components are all μg / L). In addition to the components in Table 1, five elements, Ag, Au, Cd, Hg, and Tl, were detected, and their concentrations were all ND. The industry has no requirements for other metal impurities, so other metal impurities were not detected.
[0075] Table 1 Components and contents of copper sulfate crude solution
[0076]
[0077] The water used in the following embodiments is ultrapure water, which is obtained by three filtrations. The first filtration obtains pure water with a conductivity of 5-10 μS and a total metal impurity content of <650 μg / L; the second filtration obtains RO water with a conductivity of <3 μS and a total metal impurity content of <350 μg / L; the third filtration obtains ultrapure water with a conductivity of <1 μS and a total metal impurity content of <10 μg / L.
[0078] In some specific examples of the present invention, the total metal impurity content (total gold impurities) and conductivity data of the pure water, RO water and ultrapure water used are shown in Table 2 below.
[0079] Table 2 Data of pure water, RO water and ultrapure water in some specific examples of the present invention
[0080]
[0081]
[0082] By using ultrapure water with a conductivity of less than 1μS and a total metal impurity content of less than 10μg / L as process water in each step, the introduction of metal impurities can be reduced and the purification effect of copper sulfate can be effectively improved.
[0083] Example 1
[0084] A method for purifying copper sulfate, the process flow chart is as follows Figure 1 As shown, the specific steps include:
[0085] S1. Dissolving: Dissolve the crude copper sulfate in ultrapure water at a mass ratio of 1:2.76 to obtain a crude copper sulfate solution, the specific composition content of which is shown in Table 1, wherein the copper ion content is 80 g / L;
[0086] S2, impurity removal: add hydrogen peroxide as an oxidant to the copper sulfate crude solution, add 3.33g of hydrogen peroxide with a concentration of 31wt% per 1L of copper sulfate crude solution, stir for 1h, add ammonia water as a precipitant, add 4.52g of ammonia water with a concentration of 26wt% per 1L of copper sulfate crude solution, adjust the pH value to 3.5-4, stir for 4h, let stand for 12h, filter to obtain filter residue and copper sulfate impurity removal liquid; in this step, the mass of 1L of copper sulfate crude solution is 1.189kg, so the mass ratio of the oxidant to the copper sulfate crude solution is 1:357, and the mass ratio of the precipitant to the copper sulfate crude solution is 1:263;
[0087] S3. Oil removal: Take wood activated carbon and clean it as follows: first soak the activated carbon column in 0.05 mol / L dilute sulfuric acid solution for 20 to 30 hours; then rinse the activated carbon column with ultrapure water until the conductivity of the washing water is less than 10μS; finally, when cleaning with copper sulfate solution, the total content of metal impurities in the copper sulfate washing solution is ≤1.5 mg / L, and the activated carbon after impurity removal is obtained. The specific surface area of the activated carbon is 1300m 2 / g, the activated carbon is granular activated carbon with an average particle size of 0.5-3mm, an activated carbon column filled with activated carbon after impurities removal is taken, copper sulfate impurity removal liquid is introduced into the activated carbon column, and oil removal treatment is performed to obtain copper sulfate purified liquid; the pH value of the copper sulfate impurity removal liquid is 4, and the residence time in the activated carbon is 1h;
[0088] S4, recrystallization: adding sulfuric acid to the copper sulfate purified solution to adjust the pH to 1-2 to inhibit the hydrolysis of the copper sulfate solution and to allow impurities that are easily soluble in acid to remain in the mother liquor; then evaporating and concentrating to 53% of the original solution volume, cooling and crystallizing, and using vacuum filtration for solid-liquid separation to obtain copper sulfate mother liquor and copper sulfate crystals, with a crystal yield of 50%;
[0089] S5. Washing and packaging: Use a small amount of ultrapure water to rinse the surface of the copper sulfate crystals, and obtain copper sulfate washing water and electronic grade copper sulfate after solid-liquid separation, and then add ultrapure water to dissolve, and after packaging, obtain an electronic grade copper sulfate solution with Cu=80g / L.
[0090] In the above steps, evaporation and concentration are carried out at 104°C, cooling to room temperature 20-30°C is carried out for crystallization, and the other steps are carried out at room temperature 20-30°C.
[0091] The impurity removal effect of each step was tested, and the results are shown in Table 3.
[0092] Table 3 Test results of the impurity removal effect of each step in Example 1
[0093]
[0094] Note: The impurity concentrations in Table 3 are all when Cu=80g / L.
[0095] The impurity removal step mainly removes Fe and Ti impurities, which can reduce the Fe and Ti contents to below 200 μg / L, and the Fe and Ti removal rates are both above 80%. In this step, the removal effect of other metal impurities is relatively general, and the removal rate of other metal impurities except Fe and Ti is about 10-20%.
[0096] The oil removal step is mainly to remove TOC. By utilizing the effective adsorption effect of activated carbon on organic impurities, the TOC content can be reduced to below 6 mg / L, with a removal rate of more than 80%.
[0097] The final electronic-grade copper sulfate crystals are dark blue with high purity. The purity of the electronic-grade copper sulfate is 99.999% and has a very high purity. In the electronic-grade copper sulfate solution with Cu=80g / L, the total content of metal impurities such as Fe, Ti, Al, and Ca is below 1mg / L, wherein the Fe content is <110μg / L, the Ti content is <110μg / L, and the TOC content is <3mg / L.
[0098] The purification method of Example 1 can obtain copper sulfate with high purity and low impurity content, which can be used as a product in the field of nano-scale chip integrated circuits.
[0099] Example 2
[0100] This example provides a method for purifying copper sulfate, which differs from Example 1 in that different amounts of ammonia water are added in step S2 to adjust different precipitation pH values.
[0101] The Fe and Ti concentrations in the copper sulfate impurity removal solution obtained at different precipitation pH values were detected, and the Fe and Ti removal rates were calculated. The results are shown in Table 3. Fe removal rate = (initial iron concentration - iron concentration after impurity removal) / initial iron concentration × 100%; Ti removal rate = (initial titanium concentration - titanium concentration after impurity removal) / initial titanium concentration × 100%.
[0102] Table 3 Fe and Ti removal rates at different precipitation pH values
[0103]
[0104] It can be seen from the above table that in the pH range of 2.8 to 4.0, with the increase of pH value, the removal rates of Fe and Ti both show an upward trend. In the pH range of 2.8 to 3.8, the removal rates of Fe and Ti are significantly improved. When the pH value is above 3.8, the improvement is not large. In order to avoid the precipitation of copper ions due to excessively high pH value, the optimal precipitation pH value is 3.6 to 3.8. Under this condition, impurity removal can achieve Fe removal rate of more than 85% and Ti removal rate of more than 80%. In the impurity removal step, the Fe concentration is reduced to below 200μg / L and the Ti concentration is reduced to below 150μg / L, achieving good removal effects of Fe and Ti.
[0105] Example 3
[0106] This example provides a method for purifying copper sulfate, which is different from Example 1 in that, in step S2, the amount of the copper sulfate crude solution is kept unchanged, and the amounts of the oxidant and the precipitant are changed. The specific dosage ratios are shown in Table 4.
[0107] The Fe and Ti concentrations in the copper sulfate impurity removal solution obtained under different oxidant and precipitant dosages were detected, and the Fe and Ti removal rates were calculated. The results are shown in Table 4.
[0108] Table 4 Fe and Ti removal rates at different oxidant and precipitant dosages
[0109]
[0110] Example 4
[0111] This example provides a method for purifying copper sulfate, which is different from Example 1 in that in step S4, the crystal yield of recrystallization is changed by changing the volume of the concentrated solution, and the specific crystal yield is shown in Table 5, and the metal impurity content in the electronic grade copper sulfate solution of Cu=80g / L obtained in step S5 is tested. Crystal yield = actual mass of Cu element in the crystal obtained / mass of Cu element in the solution before recrystallization treatment × 100%.
[0112] Table 5 Impurity removal effect at different crystal yields
[0113]
[0114]
[0115] It can be seen from Table 5 that when the crystal yield is too high, such as reaching 80%, the removal effect of metal impurities is poor. Only by controlling the crystal yield within an appropriate range can the crystal have a lower metal impurity content and a higher crystal purity.
[0116] In summary, the present invention adopts a specific precipitant and adjusts to a specific precipitation pH value, removes most of the Fe, Ti impurities and part of other impurities, and avoids copper ion precipitation and loss, and then combines activated carbon to remove most of the TOC impurities, and finally performs recrystallization to control a specific crystallization yield. The purity of the copper sulfate finally obtained can reach 99.999%. After the electronic-grade copper sulfate solution of Cu=80g / L is prepared, the total amount of metal impurities such as Fe, Ti, Al, Ca is below 1mg / L, wherein the Fe content is <110μg / L, the Ti content is <110μg / L, and the TOC content is <3mg / L. The copper sulfate obtained by the purification method of the present invention is electronic-grade copper sulfate, which has high purity, low total content of metal impurities and TOC content, high electroplating activity and fast electroplating speed when prepared into an electroplating solution for electroplating, and the obtained coating has uniform quality and high stability, so the electronic-grade copper sulfate of the present invention has a wide range of applications in the field of nano-chip integrated circuits.
Claims
1. A method for purifying copper sulfate, characterized in that: The following steps are involved: S1, impurity removal: adding a precipitant to the oxidized copper sulfate crude solution, adjusting the pH value to 3.6-3.8, and obtaining a copper sulfate impurity removal solution after solid-liquid separation; the precipitant comprises at least one of ammonia water, ammonium bicarbonate or ammonium carbonate; S2, degreasing: removing the oil from the copper sulfate impurity removal liquid by adsorption to obtain a copper sulfate purified liquid; S3, recrystallization: evaporating and concentrating the copper sulfate purification solution, cooling and crystallizing, controlling the crystal yield to be 20-60%, and obtaining purified copper sulfate; In step S1, the copper sulfate crude solution contains copper and metal impurity elements, and the metal impurity elements include iron and titanium; the iron content in the copper sulfate crude solution is 300-2000 μg / L; In step S1, the mass ratio of the oxidizing agent added for oxidation to the crude copper sulfate solution is 1:(100-400); the mass ratio of the precipitant to the crude copper sulfate solution is 1:(150-350).
2. The purification method according to claim 1, characterized in that In step S1, the oxidant used in the oxidation is selected from hydrogen peroxide.
3. The purification method according to claim 1, characterized in that In step S1, the oxidation reaction time is 0.5 to 2 hours; And / or, the reaction time after adding the precipitant is 1 to 10 hours.
4. The purification method according to claim 1, characterized in that In step S2, oil is removed by activated carbon.
5. The purification method according to claim 4, characterized in that The specific surface area of the activated carbon is 1000-1500m 2 / g.
6. The purification method according to claim 1, characterized in that: In step S3, before evaporation and concentration, the pH value of the copper sulfate purified solution is adjusted to 1-2.
7. The purification method according to any one of claims 1 to 6, characterized in that: The water used in each step is ultrapure water, the conductivity of the ultrapure water is ≤1 μS / cm; and / or the total content of metal impurities in the ultrapure water is ≤10 μg / L.
Citation Information
Patent Citations
Method of producing chip copper interconnection high-purity copper sulfate electroplate liquid
CN101058892A
Preparation method for electronic grade high-purity copper sulfate pentahydrate
CN103058258A